Institutional Profile: The Wolfson Centre for Personalised Medicine, University of Liverpool, Liverpool, UK. (June 2013) - Alfirevic, Ana; Carr, Daniel F; Miyajima, Fabio; Pushpakom, Sudeep; Sutton, Laura; Jorgensen, Andrea L; Pirmohamed, Munir
The Wolfson Centre for Personalised Medicine is part of the Institute of Translational Medicine at the University of Liverpool (Liverpool, UK). It houses a multidisciplinary team of personalized medicine researchers engaged in collaborative research with partners across the globe. The primary focus of the centre is the identification of predictive biomarkers of drug safety and efficacy with the aim of translation from 'bench-to-bedside'. Studies utilizing the latest genotyping and phenotyping, and point-of-care technologies, are undertaken with the ultimate aim of developing easy access for patients to truly personalized medicine. In addition to translation into clinical practice, the Centre puts significant emphasis into education of clinicians and scientists alike, as well as public engagement activities to promote personalized medicine.